Practical Strategies Using Medical Cannabis to Reduce Harms Associated With Long Term Opioid Use in Chronic Pain - MacCallum, Caroline A.; Eadie, Lauren; Barr, Alasdair M.; Boivin, Michael; Lu, Shaohua (Frontiers in Pharmacology, 2021)
BACKGROUND: Chronic non-cancer pain (CNCP) is estimated to affect 20% of the adult population. Current US and Canadian CNCP guidelines recommend careful reassessment of the risk-benefit ratio for doses greater than 90 mg morphine equivalent dose (MED), due to low evidence for improved pain efficacy at higher MED and a significant increase in morbidity and mortality. There are a number of human studies demonstrating cannabis opioid synergy. This preliminary evidence suggests a potential role of cannabis as an adjunctive therapy with or without opioids to optimize pain control. METHODS: In 2017, the Canadian Opioid Guidelines Clinical Tool was created to encourage judicious opioid prescribing for CNCP patients and to reevaluate those who have been chronically using high MED. Mirroring this approach, we draw on our clinical experiences and available evidence to create a clinical tool to serve as a foundational clinical guideline for the initiation of medical cannabis in the management of CNCP patients using chronic opioid therapy. FINDINGS: Following principles of harm reduction and risk minimization, we suggest cannabis be introduced in appropriately selected CNCP patients, using a stepwise approach, with the intent of pain management optimization. We use a structured approach to focus on low dose cannabis (namely, THC) initiation, slow titration, dose optimization and frequent monitoring. CONCLUSION: When low dose THC is introduced as an adjunctive therapy, we observe better pain control clinically with lower doses of opioids, improved pain related outcomes and reduced opioid related harm.